Solid-phase Reactor with Immobilized Lead Dioxide for Flow Injection-Spectrophotometric Determination of Naringenin in Supplement Formulations - Israa M. Jawad Al-mashhadani (Journal of Global Pharma Technology, 2018)
This study includes a simple and economic method for sensitive determine of naringenin (NAR) in (pure and supplements). The determination method depends on the oxidative coupling reaction between N, N-dimethyl-p- phenylenediamine with NAR in the present of PbO2 immobilized on cellulose acetate matrix. The reaction was carried out in alkaline medium, to form blue color product has maximum absorbance at wavelength of 596 nm. The experimental variables of solid phase reactor and flow injection parameters were investigated and optimized. Beer's law obeyed over NAR concentration range from 0.5 to 60 µg mL-1 with a sample throughput of 44 samples per hour. The solid phase material showed good stability, the relative standard deviation was 2.786 for 38 injections. The proposed method was successful for NAR determinate in supplements capsules.Keywords: Naringenin, N, N-dimethyl-p-phenylenediamine, Immobilized lead dioxide, Solid phase rector, Flow injection determination.